Roles of Oxidative Stress and Inflammation in Vascular Endothelial Dysfunction-Related Disease - Yukihito Higashi (MDPI AG, 2022)
Oxidative stress and chronic inflammation play an important role in the pathogenesis of atherosclerosis. Atherosclerosis develops as the first step of vascular endothelial dysfunction induced by complex molecular mechanisms. Vascular endothelial dysfunction leads to oxidative stress and inflammation of vessel walls, which in turn enhances vascular endothelial dysfunction. Vascular endothelial dysfunction and vascular wall oxidative stress and chronic inflammation make a vicious cycle that leads to the development of atherosclerosis. Simultaneously capturing and accurately evaluating the association of vascular endothelial function with oxidative stress and inflammation would be useful for elucidating the pathophysiology of atherosclerosis, determining treatment efficacy, and predicting future cardiovascular complications. Intervention in both areas is expected to inhibit the progression of atherosclerosis and prevent cardiovascular complications.